An enclosure design for feeding and fertilisation trials with the freshwater prawn, Macrobrachium rosenbergii (de Man) - MacLean, M.H.; Ang, K.J. (Elsevier, 1994)
The design and testing of an enclosure for experimental trials with the freshwater prawn Macrobrachium rosenbergii (de Man) is described. The suitability of the design was assessed on the basis of the physical durability of the enclosures, and on the influence of the enclosures on prawn production during a brief experiment with postlarval prawns. Two different treatments were employed in which pelleted feed was either applied at a standard commercial rate or at a decreased rate which was supplemented by fertilisation with chicken manure. The enclosures proved robust and stable, and there was no evidence to suggest that the prawns were adversely affected by confinement within the enclosures. Results from the feeding trial indicated that significantly greater prawn mean weight was achieved when organic manure partially replaced pelleted feed.